Rethinking urban design problems through morphological regions: Case of Beyazit Square - (:unkn) unknown (UNIV POLITECNICA VALENCIA, 2017)
It is highly vital to recognize the relation between urban morphology and urban design studies in city planning and urban design practices. Beyazit Square, which is the center of the city of Istanbul, could not be integrated to the other parts of the city either configurationally or socially although many design projects have been previously planned and discussed. In this study, the Historical Peninsula of Istanbul is observed as an essential unit of the traditional path reflecting each civilization, namely Roman, Byzantium, Ottoman and Republic of Turkey that have been settled in the region. Transformations in urban blocks in Beyazit region are elaborated through a series of morphological analyses based on the Conzenian approach of urban morphology. Morphological regions of the Historical Peninsula are identified and Beyazit region is addressed in detail in terms of the transformations in urban block components, that are; street, plot and buildings. The effects of surrounding units which are the mosque, university buildings, booksellers and Grandbazaar on Beyazit Square are discussed according to the morphological analyses that are applied to the region. Previous design practices and the existing plan of the area are observed through the analyses including town plan, building block, and land use patterns. It is revealed that existing design problems in Beyazit Square come from the absence of urban morphological analyses in all planning and design practices. Through morphological regions as well as the conservation plans, urban design projects can be reconsidered.
Keywords: Historical Peninsula; morphological regions; urban blocks; urban design; Beyazit Square